5 - Africa’s Growth and Development Strategies: A Critical Review - Babatunde, Musibau Adetunji (Africa Development, 2021)
At independence in the late 1950s and early 1960s, there were high hopes about the growth prospects of the new politically independent African states. Economic conditions, such as per capita real income, were comparable to other developing countries like South Korea and Taiwan. By the mid-1970s, the growth profile of most African countries had started to decline and by the mid-1980s, it became obvious that the African continent needed rescue packages which came in the form of Structural Adjustment Programmes. However, countries like Taiwan and South Korea had made tremendous progress such that their per capita real incomes had grown more than tenfold while those of most African countries had declined considerably compared to the immediate post- independence era. What role did the growth strategies adopted by African countries play in this tragedy? How do we rethink Africa’s growth strategy? What were the lessons learned and which way forward? These and other related issues are what this article sets out to address. The article identifies three distinct growth phases for the economies of Africa and analyzes critically the various models embedded in those phases. Among other things, the article strongly canvasses for the deepening of regional integration, enhancing productivity and competitiveness through investment in technology and education, and the reinventing of African labour markets to promote productivity and good labour relations.